Educational Administration and Supervision in Improving the Quality of Education at the Faculty of Medicine, Islamic University of North Sumatra - Zaim Anshari; Suci Indasari; Muammar; Siti Patimah; Nurul Hidayati Murtafiah; A. Gani (PT Inovasi Pratama Internasional, 2025)
Educational administration and supervision are two important aspects of the education system that have a strategic role in improving the quality of education. They function to manage, supervise, and develop the entire learning process at the Faculty of Medicine, Islamic University of North Sumatra. Educational administration focuses on the management of human resources, facilities, and educational policies so that learning objectives can be achieved effectively and efficiently. Meanwhile, educational supervision functions as professional development for lecturers to improve the quality of the learning process. This study aims to describe the relationship and role of educational administration and supervision in improving the quality of education at the Faculty of Medicine, Islamic University of North Sumatra. The method used is a literature study (library research) with a descriptive qualitative approach, using various sources of books, scientific journals, and laws and regulations. The results of the study indicate that integration between administration and supervision is the key to success in improving the quality of educational institutions. Effective administration supports the implementation of systematic supervision, while quality supervision strengthens the implementation of administrative functions. The collaboration of the two produces educational management that is directed, transparent, and oriented towards improving the professionalism of lecturers at the Faculty of Medicine, Islamic University of North Sumatra